Management of Sexual Dysfunction in Men and Women An Interdisciplinary Approach - Lipshultz, Larry I.; Pastuszak, Alexander W.; Goldstein, Andrew T.; Giraldi, Annamaria; Perelman, Michael A. (Springer New York : Imprint: Springer, 2016)
This book provides a comprehensive, state-of-the art review of the intersection of male and female reproductive and sexual health.  The text comprehensively discusses the evaluation and management of physical, genetic, and psychological causes of male and female sexual dysfunction. Discussion of treatment focuses on current medical and surgical psychosexual therapies in both the male and female. The book highlights erectile, ejaculatory, and orgasmic disorders in the male; desire, arousal and orgasmic disorders in the female; and an integrated approach to the couple. Lifestyle modifications through diet and exercise and optimization of anthropomorphic characteristics are also discussed, including a holistic approach to these disorders that goes beyond a focus on the genital system alone.          Sexual Dysfunction in Men and Women: An Interdisciplinary Approach serves as a resource for physicians and researchers interested in sexual medicine seeking a comprehensive overview of the practice and novel research in the field.